Pengaruh Fee Audit, Audit Tenure dan Time Budget Pressure Terhadap Kualitas Audit dengan Komite Audit Sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Dea Larasati Husodo; Wulan Retnowati; Roni Budianto (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine the effect of audit fees, audit tenure, time budget pressure on audit quality and the influence of the audit committee in moderating the influence of audit fees, audit tenure, time budget pressure on audit quality. This research is a type of quantitative research using secondary data on the annual reports of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The sample selection was carried out by purposive sampling method and obtained a sample of 40 companies that met the criteria. The analysis technique used is panel data regression analysis using Eviews 12 application. Based on the results of the analysis that has been done, it can be concluded that audit fees have a positive effect on audit quality, audit tenure does not have an effect on audit quality, time budget pressure has a negative effect on audit quality, the audit committee does not moderate the effect of audit fees and time budget pressure on audit quality, the audit committee moderates the effect of audit tenure on audit quality. These results emphasize the factors that can influence the quality of the resulting audit